Analysis of Non-Performing Loan at PT Mayora Indah in 2008 -2020 - Sabda Dian Nurani Siahaan; Elson Zega; Samuel Ardhana Sembiring; Muhammad Danuarta (Asian Journal of Applied Business and Management, 2023)
Lending by banks must pay attention to the principles of sound credit, as explained in Article 8 of Law Number 10 of 1998 concerning Banking. Banks are required to conduct thorough research on the nature, ability, capital, reserves and economic conditions of the debtor before providing credit. This study aims to prevent the possibility of bad credit. This research was conducted to find out what factors caused bad credit at PT Mayora Indah Tbk in North Sumatra. The method used in this study is descriptive qualitative using ratio analysis of NPL finance in calculating non-performing loans through the bank's balance sheet. This bad credit is also known as collectibility or bad credit and is common in the global banking industry.